PENGARUH KEMUDAHAN BERBISNIS TERHADAP INVESTASI ASING LANGSUNG: STUDI KASUS PADA NEGARA BERKEMBANG ANGGOTA ASEAN - Dianawati, Ni Luh Putu; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 10, Oktober 2018 (pp. 2071-2308), 2018)
Foreign direct investment is a source of capital that comes from abroad to home country and brings new technology from developed countries to developing countries, so that will create modernization in developing countries. The ease of doing business is one of the factors affecting foreign direct investment. This study aims to analyze the effect ease of doing business on foreign direct investment in ASEAN member developing countries in 2007-2015. The data used in this research is secondary data with analysis technique used is Fixed Effect Method. Based on the results of the analysis, simultaneously found that the ease of doing business has a significant effect on foreign direct investment. Partially trading across border and contract enforcement have a significant positive effect on foreign direct investment, while tax payments have negatively significant effect on foreign direct investment. The regulation governing cross-border trade and contract enforcement in developing member countries of ASEAN can be done easily and does not take long to attract investors to invest their capital. Key words: foreign direct investment, trading across border, contract enforcement, tax payment.